The significance of time interval between perioperative SOX/XELOX chemotherapy and clinical decision model in gastric cancer - Chen, Jun-Bing; Liu, Zi-Ning; Wang, Yin-Kui; Shan, Fei; Li, Shuang-Xi; Jia, Yong-Ning; Xue, Kan; Miao, Ru-Lin; Li, Zhe-Min; Wu, Zhou-Qiao; Ying, Xiang-Ji; Zhang, Yan; et al. (Frontiers in Oncology, 2022)
Introduction To investigate the influences of time interval between multimodality therapies on survival for locally advanced gastric cancer (LAGC) patients, 627 patients were included in a retrospective study, and 350 who received neoadjuvant chemotherapy (NACT) based on SOX (S-1 plus Oxaliplatin)/XELOX (Capecitabine plus Oxaliplatin) treatment, radical surgery, and adjuvant chemotherapy (AC) from 2005.01 to 2018.06 were eligible for analyses. Methods Three factors were used to assess influences, including time interval from NACT accomplishment to AC initiation (PECTI), time to surgery after NACT accomplishment (TTS), and time to adjuvant chemotherapy after surgery (TAC). Results Concerning PECTIs, 99 (28.29%) experienced it within 9 weeks, 188 (53.71%) within 9–13 weeks, 63 (18.00%) over 13 weeks. Patients’ 5-year overall survival (OS) significantly decreased as trichotomous PECTI increased (78.6% vs 66.7% vs 55.7%, P = .02). Analogously, there was a significant decrease for dichotomous TTS (within vs over 5 weeks) in OS (P = .03) and progression free survival (PFS) (P = .01) but not for dichotomous TAC (within vs over 6 weeks) in OS and PFS (P = .40). Through multivariate Cox analyses, patients with PECTI over 13 weeks had significantly worse OS (P = .03) and PFS (P = .02). Furthermore, extended TTS had significantly worse OS and PFS but insignificantly worse OS and PFS than extended TAC. Therefore, gastric patients receiving perioperative SOX/XELOX chemotherapy and surgery with extended PECTI over 9 weeks or TTS over 5 weeks would have a negative correlation with PFS and OS, and worse when PECTI over 13 weeks. Nomograms (including PECTI, ypT, ypN, Area Under Curve (AUC) = 0.81) could predict patient survival probability and guide intervention with net benefit. Discussion In control of PECTI, TTS could be extended appropriately, and shortened TAC might make a remedy, and delayed TAC might be allowed when TTS was shortened.